2020
DOI: 10.1097/gox.0000000000003104
|View full text |Cite
|
Sign up to set email alerts
|

Thoracodorsal Artery Perforator Flap in Partial Breast Reconstruction: A Systematic Review

Abstract: Introduction: Breast conserving surgery followed by radiation therapy represents the standard of care for early stage breast cancer. Oncoplastic breast surgery includes several reconstructive techniques essentially summarized in 2 categories: volume displacement and volume replacement procedures. These latest procedures have evolved over time from the use of the entire latissimus dorsi muscle to the use of pedicled perforator flaps, namely the thoracodorsal artery perforator (TDAP) flap. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…A number of studies have reported, through small and medium series of patients, on the safety of tissue replacement techniques during oncoplastic lumpectomy. 3 , 5 , 6 , 8 , 15 , 17 20 , 23 26 With regards to the oncological safety of these flaps, authors have reported different management of positive margins post oncoplastic reconstruction using tissue replacement techniques. Meybodi et al had one positive margin managed with reexcision.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported, through small and medium series of patients, on the safety of tissue replacement techniques during oncoplastic lumpectomy. 3 , 5 , 6 , 8 , 15 , 17 20 , 23 26 With regards to the oncological safety of these flaps, authors have reported different management of positive margins post oncoplastic reconstruction using tissue replacement techniques. Meybodi et al had one positive margin managed with reexcision.…”
Section: Discussionmentioning
confidence: 99%
“…In general, OPS has limited postoperative complications ( 11 , 30 , 37 ), low re-resection rates ( 25 , 29 ), and the cosmetic outcome is acceptable with high patients’ satisfaction ( 11 , 36 - 38 ). Furthermore, OPS is safe with high overall and disease-free survival rates ( 21 , 23 - 25 ).…”
Section: Key Contents and Findingsmentioning
confidence: 99%
“…Según Mangialardi et al 12 . el TDAP permite la reconstrucción mamaria en resecciones >20% del volumen, alcanzando resultados satisfactorios en 80 -94% de los casos, con tasas de complicaciones (seromas y morbilidad del sitio donante) muy bajas, representando una alternativa efectiva y versátil 12 .…”
Section: Tipos De Bct-opunclassified
“…El tratamiento quirúrgico tiene el rol más importante en el control locorregional del cáncer de mama temprano y cáncer de mama localmente avanzado (CMLA) 9,10 . Las técnicas quirúrgicas han evolucionado mucho desde la mastectomía radical de Halsted (1882) que, pese a mejorar la supervivencia de las pacientes, generó una gran morbilidad postoperatoria por ser mutilante 9 , ésta fue reemplazada en los años 70 por la mastectomía radical modificada de Madden, que a diferencia de la anterior, preserva los músculos pectorales y permite una mejor función del miembro superior mediante la linfadenectomía de los niveles ganglionares I y II; mostrando idéntica tasa de supervivencia con menor morbilidad, convirtiéndose en el estándar de tratamiento para pacientes con cáncer de mama temprano, que tienen contraindicaciones para la cirugía conservadora de mama convencional (BCS) [11][12][13] .…”
Section: Introductionunclassified